Basic psychological skills usage and competitive anxiety responses: Perceived underlying mechanisms - Wadey, R.; Hanton, S. (Research Quarterly for Exercise and Sport, 2008)
This study examined the relationship between basic psychological skills usage (i.e., goal-setting, imagery, self-talk, and relaxation) and the intensity and directional dimensions of competitive anxiety. Semistructured interviews were used on a sample of 15 elite athletes (M age = 24.3 years, SD = 4.2) from a variety of team and individual sports. Findings revealed that the participants maintained the intensity of their anxiety response prior to competition and could deploy goal-setting, imagery, or self-talk to enable facilitative interpretations of anxiety-related symptoms to performance. Higher levels of self-confidence and an optimistic outlook toward forthcoming competition were also expressed. The underlying mechanisms perceived to be responsible for these effects included effort and motivation, attentional focus, and perceived control over the anxiety response.